Women’s empowerment in agriculture and dietary diversity in Ethiopia - Yimer, Feiruz; Tadesse, Fanaye (International Food Policy Research Institute, 2015)
Intra-household resource allocation has a considerable role to play in nutritional status in developing countries. Maternal and children’s dietary diversity are linked, not only with the circumstances of the household in general, but also with the status of women in particular. The extent to which women have access to and control over re-sources largely determines the kind of care they provide for their children and for the rest of the household. As recognized by the National Nutrition Program, women’s lack of control over household resources, time, knowledge, and social support networks constitutes a major barrier to improving poor nutritional outcomes in Ethi-opia. Using household survey data from 2013, we investigate the impact of women’s empowerment in agriculture on the nutrition outcomes of children and women. The data were collected in five regions of the country from more than 7,000 households in 84 woredas. We use multivariate regression methods and instrumental variable tech-niques to establish the relationship between women’s empowerment and the dietary diversity of women and chil-dren. The results indicate that all of the women’s empowerment indicators used are positively related to better die-tary diversity for both children and women. As women’s empowerment leads to improvements in children’s and women’s dietary diversity, it follows that interventions which increase women’s empowerment contribute to im-proving child nutrition as well as their own well-being.